Pemanfaatan Google Meet Dan Classroom Pada Media Pembelajaran Di PKBM Bina Bangsa - Ratna Kusumawardani; Rusdah; Setiono, Devit; Kusumaningsih, Dewi; Syafrullah, Muhammad (Ikatan Ahli Informatika Indonesia, 2024)
Currently, learning media in Indonesia uses ICT-based learning media. This is because all learning institutions and educational institutions apply blended learning, namely offline (offline) and online (online) in the process of teaching and learning activities. Using good and appropriate learning media can make it easier for students to digest learning material. One of the educational institutions that carries out online teaching and learning activities is PKBM Bina Bangsa Tangerang. This institution has a role in training people's skills and independence. However, some students have not mastered using Google Meet and Google Classroom in teaching and learning activities. To fulfill this, we are collaborating with PKBM Bina Bangsa Tangerang to conduct training on using Google Meet and Google Classroom. This activity aims to ensure that students understand how to use Google Meet and Google Classroom in the teaching and learning process so that students can receive the material provided by the teacher well. This training applies a practicum method involving 16 students which was carried out online on October 21, 2023. Based on the questionnaire data that has been processed, it shows that this activity was well received by the students and the students understood the facilities available. found in Google Meet as much as 90% and understanding regarding the use of Google Meet as much as 91%. Then the students' understanding regarding the facilities available in Google Classroom was 87% and their understanding regarding the use of Google Classroom was 86%